Faktor – Faktor Dampak Kebijakan Larangan Import Pada Penjualan Thrift Di Kota Tangerang - David Anthonyus; Suparman (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to analyze the factors affecting the impact of the government’s policy on banning the importof second-hand clothing on thrift business sales in Tangerang City. The import ban policy was implementedto protect the domestic garment industry and to safeguard public health. However, this policy has generatedvarious consequences for thrift business actors who have long depended on imported second-hand clothingas their main source of supply. This research employs a descriptive qualitative approach. Data werecollected through in-depth interviews and documentation studies. The informants consisted of governmentrepresentatives, thrift business owners in Tangerang City, and academics with expertise in trade policy andmicro-enterprises. Data analysis was conducted qualitatively through data reduction, data presentation, andconclusion drawing. The findings indicate that the import ban policy has resulted in economic impacts,including decreased income, limited product supply, and increased selling prices of thrift products. From asocial perspective, the policy has influenced public perceptions of thrift businesses and altered consumerconsumption patterns. Meanwhile, in terms of business operations, thrift entrepreneurs face reduced stockavailability and limited product variety. To cope with these conditions, thrift business actors haveimplemented various adaptive strategies, such as product diversification, seeking alternative suppliers, andstrengthening relationships with customers. However, these strategies remain defensive in nature and havenot yet been fully effective in promoting optimal business development.Keywords: Import Ban Policy, Policy Impact, Second-Hand Clothing, Tangerang City, ThirftBusiness